2023
DOI: 10.1002/agr.21831
|View full text |Cite
|
Sign up to set email alerts
|

Consumers bahavior towards the country of origin labeling policy: The case of the pasta market in Italy

Fabio Boncinelli,
Andrea Dominici,
Federico Bondioni
et al.

Abstract: This study investigates the effect on the demand of pasta following the introduction of the mandatory country of origin labeling for wheat in Italy. This regulation opened a debate between producers, farmers, and consumer organizations on the opportunity posed by this policy. Using an online survey with a choice experiment conducted on 551 Italian pasta consumers, we demonstrated that consumers strongly approve this mandatory policy. This support suggests that place of wheat origin is relevant in driving the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Studies have analyzed consumers’ attitudes, acceptance, and preferences for several of pasta’s characteristics across various geographic locations, such as Italy, Poland, Australia, etc. A wide array of research methods, encompassing both qualitative (e.g., focus groups) and quantitative (e.g., means–end analysis and choice-based analysis) techniques, were employed [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These studies found that consumers primarily base their pasta choices on a few attributes, like wheat origin, brand, and price [ 8 , 13 , 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies have analyzed consumers’ attitudes, acceptance, and preferences for several of pasta’s characteristics across various geographic locations, such as Italy, Poland, Australia, etc. A wide array of research methods, encompassing both qualitative (e.g., focus groups) and quantitative (e.g., means–end analysis and choice-based analysis) techniques, were employed [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These studies found that consumers primarily base their pasta choices on a few attributes, like wheat origin, brand, and price [ 8 , 13 , 19 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A wide array of research methods, encompassing both qualitative (e.g., focus groups) and quantitative (e.g., means–end analysis and choice-based analysis) techniques, were employed [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These studies found that consumers primarily base their pasta choices on a few attributes, like wheat origin, brand, and price [ 8 , 13 , 19 , 20 , 22 ]. In detail, Italian consumers show a strong preference for pasta made from Italian durum wheat.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations